2020
DOI: 10.3390/cancers12071803
|View full text |Cite
|
Sign up to set email alerts
|

Epitope Mapping and Computational Analysis of Anti-HPV16 E6 and E7 Antibodies in Single-Chain Format for Clinical Development as Antitumor Drugs

Abstract: Human Papillomavirus 16-associated cancer, affecting primarily the uterine cervix but, increasingly, other body districts, including the head–neck area, will long be a public health problem, despite there being a vaccine. Since the virus oncogenic activity is fully ascribed to the viral E6 and E7 oncoproteins, one of the therapeutic approaches for HPV16 cancer is based on specific antibodies in single-chain format targeting the E6/E7 activity. We analyzed the Complementarity Determining Regions, reposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Recently, we also compared our scFvs to Clinical-Stage Therapeutic antibodies (CSTs) by computational analysis, and observed that they have properties well-conforming antibodies which have already reached Phase I clinical trial [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we also compared our scFvs to Clinical-Stage Therapeutic antibodies (CSTs) by computational analysis, and observed that they have properties well-conforming antibodies which have already reached Phase I clinical trial [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Single-chain variable antibody fragments (scFvs) are another area of interest in antitumor management, especially with respect to HPV. These antibodies can be engineered for expression intracellularly, or to target cells directly [47]. Specifically, scFvs have been identified with the ability to bind to epitopes of oncoproteins expressed by HPV-16 (16E7) and interfere with protein function [47].…”
Section: Future Of Hpv Vaccinationmentioning
confidence: 99%
“…These antibodies can be engineered for expression intracellularly, or to target cells directly [47]. Specifically, scFvs have been identified with the ability to bind to epitopes of oncoproteins expressed by HPV-16 (16E7) and interfere with protein function [47]. Other scFvs have been identified that could work by interfering with E7 binding to the pRb tumor suppressor directly [47].…”
Section: Future Of Hpv Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific antibodies in a single-chain format (scFvs) able to target the E6 and E7 oncoproteins of high-risk HPVs represent new therapeutic molecules against HPV-associated neoplastic lesions. Amici et al evaluated the antigen-binding capacity of diverse anti-16E7 scFvs by using E7 mutants as well as by performing computational analyses to define length, total net charge, hydrophobicity, polarity, and charge distribution to better adapt the antibodies for clinical use [ 19 ]. Hence, scFvs may represent valid candidates for HPV-related cancer immunotherapy.…”
mentioning
confidence: 99%